Українська скульптура - Горєлов, Д. О. (ХНУРЕ, 2020)
The world of sculpture in our life is presented brightly and varied. For many centuries, talented craftsmen create their works. In his sculptural creations, the artist expresses the spiritual world, ideas about the environment, embodies his aesthetic ideals, fantasies. What role can sculpture play in our life?
Keywords: Українська скульптура; українознавство; традиції; культура